Dinamika Multikulturalisme dan Multilingualisme dalam Masyarakat Jepang - Ni Putu Luhur Wedayanti; Ni Made Andry Anita Dewi; Ni Putu Candra Lestari (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Udayana, 2026)
The dynamics of globalisation and demographic issues have forced Japan to open its doors wide to accept an increasing influx of migrant workers. The homogeneous and monolingual background of Japanese society is often cited as the cause of pros and cons regarding the presence of foreigners in Japan. Multiculturalism and multilingualism are ideologies that are contrary to the monoculturalism and monolingualism of Japanese society. This ideology has led to a society that is less accepting of differences in cultural and linguistic backgrounds within its own country, demanding assimilation or cultural adaptation that is not mutually agreed upon